General pedagogical knowledge in the design and development of significant learning experiences for teacher education - Del Moral Santaella, Cristina (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The skills to design meaningful and self-regulated learning experiences to produce a understanding in students, is a key skill that defines teachers, without which they cannot face the daily tasks of your job properly as it is a basic element to achieve effective teaching. This paper presents general pedagogical knowledge necessary that the teacher must have to develop the ability to design meaningful learning experiences, general pedagogical knowledge that can be applied in all levels of education, from kindergarten to levels higher grades for the construction of educational programming units.